Protolytic Reactions of 3,6-DI-tert-Butyl-2-Hydroxyphenoxyl with Nitrogen Bases - Masalimov, A. S.; Tur, A. A.; Nikolskiy, S. N. (Springer US, 2016)
Stable phenoxyl radicals were used as spin probes for the EPR spectral determination of the kinetic basicity of amines, nitrogen heterocycles, alkaloids, and of rate constants for rapid intermolecular proton exchange with various NH-acids in nonaqueous media. An analysis was carried out on the effect of the solvation properties of the medium on the EPR spectral parameters of the components of acid–base reactions required for spectral kinetic investigations.
Keywords: phenoxyl radical; protolytic reactions; nitrogen bases; EPR spectra